1580. In Vitro Activity of Ceftazidime-Avibactam Against Enterobacterales and Pseudomonas aeruginosa Collected in Latin America as part of the ATLAS Global Surveillance Program, 2017-2019. (31st December 2020) - Kazmierczak, Krystyna; Valente, Maria Lavinea; Lemos, Elkin; Baudrit, Monique; Quintana, Alvaro; Irani, Paurus; Stone, Greg; Sahm, Daniel F
Abstract: Background: Ceftazidime-avibactam (CAZ-AVI) is a β-lactam/non-β-lactam β-lactamase inhibitor combination with in vitro activity against Enterobacterales (Ent) and Pseudomonas aeruginosa ( Psa ) carrying Class A, C and some Class D β-lactamases. We examined the in vitro activity of CAZ-AVI and comparators against isolates collected in Latin America (LA) as part of the ATLAS surveillance program. Methods: Non-duplicate isolates of Ent (n=8416) and Psa (n=2521) were collected in 10 countries in Central America (CAC; Costa Rica, Dominican Republic, Guatemala, Panama [2018-2019 only]) and South America (SA; Argentina, Brazil, Chile, Colombia, Mexico, Venezuela [2017-2019]). Susceptibility testing was performed by CLSI broth microdilution and values were interpreted using CLSI 2020 breakpoints. CAZ-AVI was tested at a fixed concentration of 4 µg/mL AVI. Isolates with meropenem (MEM) MICs ≥2 µg/mL (Ent) or ≥4 µg/mL ( Psa ) were screened for β-lactamase genes. Results: CAZ-AVI demonstrated potent in vitro activity against Ent collected in LA overall and in the CAC and SA subregions (95-99% susceptible (S)) that was comparable to or exceeded the activity of comparators including MEM, amikacin (AMK) and tigecycline (TGC) (Table). CAZ-AVI retained good activity against MEM non-susceptible (NS) Ent collected in SA (82% S; 6.9% of collected isolates) but activity was reduced against MEM-NS Ent from CAC (10% S; 5.7% of collected isolates), which included a high proportion of isolates carrying NDM-type metallo-β-lactamases (MBL). Among Psa, CAZ-AVI showed greater activity than the tested comparators against both all (86-92% S) and MEM-NS (61-66% S) isolates collected in LA overall and in the two subregions. Table Conclusion: CAZ-AVI showed potent in vitro activity against Ent and Psa collected from patients in the CAC and SA subregions of LA. Activity was also good against MEM-NS isolates from SA but was reduced against MEM-NS Ent from CAC that included a high proportion of MBL-positive isolates. The regional and country prevalence of different carbapenem-resistance mechanisms must be considered when evaluating treatment options; however, CAZ-AVI could provide a valuable therapeutic option for treatment of infections caused by Ent and Psa in LA. Disclosures: Krystyna Kazmierczak, PhD, IHMA (Employee)Pfizer, Inc. (Consultant) Maria Lavinea Valente, MD, Pfizer Brazil (Employee) Elkin Lemos, MD, PhD, Pfizer Columbia (Employee) Monique Baudrit, MD, MSc, Pfizer Costa Rica (Employee) Alvaro Quintana, MD MSc, Pfizer, Inc. (Employee) Paurus Irani, MD, Pfizer United Kingdom (Employee) Greg Stone, PhD, AztraZeneca (Shareholder, Former Employee)Pfizer, Inc. (Employee) Daniel F. Sahm, PhD, IHMA (Employee)Pfizer, Inc. (Consultant)Shionogi & Co., Ltd. (Independent Contractor)